Reconsider the psychosis and autism concepts - Willemart, Philippe (Clinical Styles. The Journal on the vicissitudes of childhood, 1999)
The research and practice of Maria Cristina Kupfer on Lugar de Vida question the generally accepted notions of structure, subject, autism and psychosis. The following text aims to highlight the differences between psychosis and autism. If these differences are acknowledged in this form, children should benefit from a different kind of treatment.